Formative assessment: Evaluating the effectiveness of online quizzes in a core business finance course - Hamish Anderson (Flexible Learning Association of New Zealand, 2011)
This article examines the change from conventional pen and paper to computer-based formative assessment for a large second-year Business Finance course. A brief history of the course's formative assessment, its weaknesses, and the challenges for effective administration of the course are presented. These weaknesses and challenges led to a change of practice to online mastery quizzes that enable students to gauge whether they have attained the level of base knowledge and comprehension they need to successfully negotiate the course's higher-level learning outcomes. Introducing the mastery quiz formative assessment system required a large upfront investment in both time and money. However, very large savings in variable costs and (in particular) time have resulted since the change was implemented. Analysis of the 2008 distance cohort shows that completion and mastery of the online quizzes is a strong predictor of student performance in summative assessment. The analysis also shows that formative assessment is beneficial to borderline and academically weak students and that it is better for students to use the formative assessment too late, than not at all.